TO INCOME SMOOTHING (EMPIRICAL STUDY AT COMPANY WHICH ENLIST IN BEI) - Hupoyo, Sutrisno; Isnugroho, Drajat (Jurnal Analisis Bisnis Ekonomi, 2009)
This research aim to test the influence of return on equity, debt to equity, company size, dividend payout ratio and net profit margin to action of income smoothing done by a company enlisted in BEI which do not the including company of banking and finance in the year 2004 until year 2007. Based of sample intake method by purposive sampling. Result from intake sample obtained by 33 company. Research method use the descriptive statistical analysis, test the classic assumption and analyse the linear regression. Result of research indicate that by parsial, debt to equity, company size, dividend payout ratio and net profit margin don't have the influence signifikan to action of income smoothing done by a company. While return on equity have the positive influence of signifikan to actionof income smoothing done by a company. Result from coefficient determinasi indicate that still many other sactor having an effect on to action of income smoothing by a company. Research here in after shall add the variable, like ownership of government, structure of ownership of and bonus plan.